Awareness, departure, and preparation time in no-notice wildfire evacuations. (July 2021) - Grajdura, Sarah; Qian, Xiaodong; Niemeier, Deb
Highlights: Age, race, and income all have a large and significant effect on when someone is first alerted to the wildfire. Smartphones have a large and positive effect on awareness time. Community evacuation plans improve no-notice fire awareness time. Abstract: No-notice wildfires pose a serious threat to the safety of residents, where the notification time and departure time may all be within a matter of minutes. Here, we examine the factors associated with the initial wildfire awareness time, the evacuation preparation time, and finally the departure time. We use unique interview and survey data gathered in Red Cross shelters just weeks after evacuation for the 2018 Camp Fire in Northern California. We specify models for awareness time, departure time, and preparation time and find that quicker awareness is associated with seeing the fire first-hand, familiarity with local evacuation protocol, smartphone ownership, among others. We find that higher incomes are associated with quicker awareness, but had no effect on departure or preparation times. Longtime residents had longer preparation and departure times. Taken together, our results suggest new pathways for better understanding how to plan and prepare for no-notice disaster events.